Adaptive Logic Characterizations of Input/output Logic - Straßer, Christian; Beirlaen, Mathieu; Van De Putte, Frederik (Studia Logica, 2016)
We translate the unconstrained and constrained input/output-logics from [17, 18] to reflexive modal logics, using adaptive logics for the constrained case. The resulting reformulation has various advantages. First, we obtain a proof-theoretic (dynamic) characterization of input/output logics. Second, we demonstrate that our modal framework gives naturally rise to useful variants. Finally, the modal logics display a gain in expressive power over their original counterparts in the input/output framework.